2014
DOI: 10.1007/s11071-014-1774-6
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical complexity and stochastic resonance in a bistable system with time delay

Abstract: This paper addresses the problem of stochastic resonance (SR) in a time-delayed bistable system subjected to Gaussian white noise. Differing from the conventional studies, the statistical complexity measure and the normalized Shannon entropy have been defined and employed to quantify SR phenomenon of the time-delayed bistable system. According to the definitions of statistical complexity measure and normalized Shannon entropy, a minimum of entropy illustrates that the motion of system reaches some degree of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, it can be observed from spectrogram in Figure 2 that, beyond −14.4 dB, the presence of the ship signal is not recognizable in ambient noise. One study [38] has shown that SNR has good agreement with SCM. This feature enabled the SCM to describe stochastic resonance by comparing with the SNR [38].…”
Section: Simulation Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it can be observed from spectrogram in Figure 2 that, beyond −14.4 dB, the presence of the ship signal is not recognizable in ambient noise. One study [38] has shown that SNR has good agreement with SCM. This feature enabled the SCM to describe stochastic resonance by comparing with the SNR [38].…”
Section: Simulation Resultsmentioning
confidence: 95%
“…One study [38] has shown that SNR has good agreement with SCM. This feature enabled the SCM to describe stochastic resonance by comparing with the SNR [38]. To ensure that the results presented in Figure 3 are not due to stochastic fluctuations, we computed H SCM and C SCM for the ship signal at´19.2 dB and ambient noise at every 9 s (60 s duration, segregated to form seven signals, each of duration 9 s).…”
Section: Simulation Resultsmentioning
confidence: 95%
“…It is a well-established fact nowadays that a suitable amount of noise can result in an improved performance of certain nonlinear systems, and such favorable use of injected noise is the so-called stochastic resonance phenomenon [1][2][3]. In recent years, the phenomenon of stochastic resonance has been the subject of considerable interest in various research fields, such as physics [4][5][6][7], biomedicine [8], signal processing [9,10] and neural networks [11][12][13]. However, a complicated question is to characterize the optimal level, or even better the optimal probability density function (PDF), of the noise to be purposefully injected in a given nonlinear process in order to maximize the performance.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many theoretical developments of SR in conventional bistable systems [7][8][9][10][11][12]. Recently, there have appeared some extensions of SR, such as stochastic resonance in a harmonic oscillator [13], ghost stochastic resonance in the FitzHugh-Nagumo neuron model [14,15], Transition in a Bistable Duffing System [16], time delay SR [17], trichotomous noise induced SR in a linear system [18], and superthreshold SR [19]. Literature [20][21][22] proposes a new model of multistable system.…”
Section: Introductionmentioning
confidence: 99%
“…Literature [20][21][22] proposes a new model of multistable system. However, [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] did not study the SNR. In this paper, we use the model of multistable system driven by periodic signal and white noise which can realize the maximum utilization of noise and obtain better detection effects.…”
Section: Introductionmentioning
confidence: 99%